Crystallization and X-ray diffraction analysis of human CLEC5A (MDL-1), a dengue virus receptor - Watson, A; Ocallaghan, C (2009)
The human C-type lectin-like protein CLEC5A (also known as MDL-1) is expressed on the surface of myeloid cells and plays a critical role in dengue-virus-induced disease by signalling through the transmembrane adaptor protein DAP12. The C-type lectin-like domain of CLEC5A was expressed in Escherichia coli, refolded and purified. Recombinant CLEC5A crystals were grown by sitting-drop vapour diffusion using polyethylene glycol 6000 as a precipitant. After optimization, crystals were grown which diffracted to 1.56 Å using synchrotron radiation. The results presented in this paper suggest that crystals producing diffraction of this quality will be suitable for structural determination of human CLEC5A. © 2010 International Union of Crystallography All rights reserved.